APLIKASI TRACER STUDY BERBASIS WEB PADA UNIVERSITAS DIPONEGORO - Adi Soetrisno, Yosua Alvin (Transmisi: Jurnal Ilmiah Teknik Elektro, 2019)
This study aims to integrate the alumni information system which has not been integrated at Diponegoro University. The alumni information system previously encountered problems, namely the absence of alumni database application standards, and there was no policy requiring students to fill and update the alumni database system. The application designed in this study can be a medium that connects faculties and also requires that each alumni can fill in the data in the database. The system development method used in developing this system is the V model. This application has the facility to update work data and first salary when working. Information entered into the application can facilitate primary data collection for accreditation purposes. In this application alpha testing is done using the blackbox testing method and in beta testing using a questionnaire distribution method to input applications. Of the graduates in 2017 there are 4521 alumni who have filled in the data well, and there is an increase in 2018 as many as 6487 which indicates that this application can be a means to meet alumni data needs.